Identification of key genes and immune infiltration of diabetic peripheral neuropathy in mice and humans based on bioinformatics analysis - Zhang, Yumin; Zhou, Hui; Liu, Juan; Zhou, Nan (Frontiers in Endocrinology, 2024)
Background Diabetic peripheral neuropathy (DPN) is a common chronic complication of diabetes, while the underlying molecular mechanisms are still unclear. The aim of this study was to screen the key genes and the roles of immune infiltration in DPN using bioinformatics analysis. Methods DPN mice datasets including GSE222778, GSE11343, GSE70852, GSE27382, and GSE34889 were retrieved from the GEO database. Data of human DPN were retrieved from the dbGaP. The differentially expressed genes (DEGs) were selected and further analyzed by using Gene Ontology, Kyoto Encyclopedia of Genes and Genomes enrichment analysis, and Gene Set Enrichment Analysis (GSEA) to find the shared key pathway. Protein–protein interaction networks were built in shared mouse and human DEGs. The hub genes were selected and verified in vitro using high- glucose-treated PC12 cells and Schwann cells. The single-sample GSEA (ssGSEA) algorithm was used to analyze the proportions of infiltrating immune cells in human DPN and the subsequent correlations with hub genes. Results A total of 323 mouse DEGs and 501 human DEGs were selected, and they were found significantly enriched in immune-related biological functions and pathways. A total of 13 DEGs were found shared in mice and human DPN datasets, and among them, there were 7 hub genes, namely, PLAUR, S100A8, IL7R, CXCL13, SRPX2, CD300LB, and CFI. The expression of Cfi, S100a8, Cxcl13, and Cd300lb was consistently confirmed in vitro. The scores of neutrophils and NK CD56bright cells varied most significantly by immune cell infiltration analysis (p < 0.01). Furthermore, the selected hub genes were found to be highly correlated with the immune infiltration. Conclusion Our study indicated the importance of immune dysregulations in DPN and identified several hub genes through combined analysis in mice and human DPN samples, thus providing potential diagnostic and therapeutic targets in the future.